2015
DOI: 10.1177/2153368715586633
|View full text |Cite
|
Sign up to set email alerts
|

Criminal Justice Involvement, Drug Use, and Depression Among African American Children of Incarcerated Parents

Abstract: The incarcerated population in the United States is disproportionately African American and many inmates are parents of children under the age of 18. Recent reports show that African American children were significantly more likely than White children to have a parent in prison. Emerging research has also begun to investigate some of the effects that parental incarceration can have on children, but little has focused exclusively on the population of African American youth. This study draws on the National Long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…The current study supports evidence suggesting parental incarceration may influence substance use risk (Kopak and Smith-Ruiz, 2015; Roettger et al, 2011) and expands our understanding of the potential effects of parental incarceration by documenting the link to sexual risk behavior and STI. Our group has documented incarceration impacts the risk not only of those who have been incarcerated but also that of their primary committed partners, and findings suggest incarceration likely has influences on the STI/HIV risk of the larger social and sexual network (Khan et al, 2009a; Khan et al, 2011; Khan et al, 2008).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The current study supports evidence suggesting parental incarceration may influence substance use risk (Kopak and Smith-Ruiz, 2015; Roettger et al, 2011) and expands our understanding of the potential effects of parental incarceration by documenting the link to sexual risk behavior and STI. Our group has documented incarceration impacts the risk not only of those who have been incarcerated but also that of their primary committed partners, and findings suggest incarceration likely has influences on the STI/HIV risk of the larger social and sexual network (Khan et al, 2009a; Khan et al, 2011; Khan et al, 2008).…”
Section: Discussionsupporting
confidence: 81%
“…Parental incarceration may have particularly important implications for non-white children due to the marked racial/ethnic disparity in incarceration; though blacks comprise only 13% of the US population (United States Census Bureau, 2015) half of children who have an incarcerated parent are black (Bureau of Justice Statistics, 2010). There is an established relationship between parental incarceration and substance use (Kopak and Smith-Ruiz, 2015; Murray et al, 2012; Roettger et al, 2011), and, though less well researched, sexual risk behavior during adolescence (Nebbitt et al, 2014; Whalen and Loper, 2014) and adulthood (Hillis et al, 2001; Hillis et al, 2000) and HIV infection in adulthood (Lee et al, 2013). An important gap in the extant literature however is knowledge of how the age of the child during a parental incarceration influences risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental incarceration groups in this study also used drugs at an earlier age compared to those who did not experience the incarceration of a parent. Lastly, [9] work showed that the children of incarcerated parents were more than 3 times as likely to qualify for substance use disorders by late adolescence as those who did not have a parent incarcerated.…”
Section: Maternal Incarceration and Drug Usagementioning
confidence: 99%
“…Hence, children are more likely to depend on drugs as a method to cope with the shame associated with having a parent incarcerated [9] [21]. Analyses of the National Longitudinal Study of Adolescent to Adult Health (Add Health), determined that having a father incarcerated increased the frequency of marijuana use by a factor of 1.77 for male children and a factor of 1.75 for female children [21].…”
Section: Maternal Incarceration and Drug Usagementioning
confidence: 99%